Treatment and Prevention of Lung Cancer Using a Virus-Infected Reprogrammed Somatic Cell-Derived Tumor Cell Vaccination (VIReST) Regime - Zhang, Zhe; Lu, Shuangshuang; Dunmall, Louisa S. Chard; Wang, Zhizhong; Cheng, Zhenguo; Zhang, Zhongxian; Yan, Wenli; Chu, Yongchao; Gao, Dongling; Wang, Na; Li, Yang; Wang, Jiwei; et al. (Frontiers in Immunology, 2020)
Lung cancer remains the most commonly diagnosed cancer and despite therapeutic advances, the associated mortality remains high. The long period of clinical latency associated with lung cancer provides an ideal window of opportunity to administer vaccines to at-risk individuals, which can provoke immune reactions against tumor cells to provide both therapeutic benefit and long-term protection. Here we describe a Virus-Infected, Reprogrammed Somatic cell-derived Tumor cell (VIReST) regime for prevention of lung cancer. Personalized lung cancer cells were derived from induced pluripotent stem cells, which were pre-infected with oncolytic Adenovirus or Vaccinia virus prior to delivery of vaccines sequentially to an inducible transgenic model of lung cancer. iPSC-derived lung cancer cells were highly antigenically related to lung cancer cells induced in LSL-KRasG12D/+; Trp53R172H/+ transgenic mice. These cells were antigenically unrelated to original pluripotent stem cells or pancreatic cancer cells derived using the same technological platform. Application of the VIReST regime primed tumor-specific T cell responses that significantly prolonged survival in the induced transgenic model of lung cancer. These results demonstrate that antigenically relevant whole tumor cell vaccines can be derived from an individuals’ stem cells and can be applied prior to disease development to delay disease onset. This technology provides a platform for development of personalised prophylaxis that may ultimately prevent disease emergence in at-risk individuals.